Kawasaki disease in children from Dubai, United Arab Emirates (2012-2020): a single-centre retrospective clinical case series - Tom Loney; Ruzaina Sait; Aida Joseph Azar; Sam Hassan (BMJ Publishing Group, 2022)
Kawasaki disease (KD) is most common among East Asian children. There is a lack of data from Middle Eastern countries. We conducted a retrospective study of 27 paediatric patients with KD in Dubai, United Arab Emirates, 2012-2020. The majority of the patients were male, Asian, aged 1-5 years and presented with typical (complete) KD. Timely high-dose intravenous immunoglobulins were administered to 18 patients. Twelve patients did not develop any cardiac complications, 12 had a coronary artery aneurysm and 2 patients developed serious cardiac complications . No patient experienced non-cardiac complications or died. Paediatric patients with KD in Dubai were similar to those from other countries.